Analisis Penerapan Pengendalian Internal Dalam Mendeteksi Serta Mencegah Kemungkinan Adanya Tindakan Fraud Pada UMKM - Sherly Aulia Absari; M. Cholid Mawardi; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
This study aims to determine the effect of implementing internal control at two MSME locations by explaining aspects of internal control implemented by business actors to prevent fraud in two UMKM in Malang City as a form of comparison between one business and another. This research is descriptive research using a qualitative approach. The data collection method was carried out by means of observation and interviews with related parties. Based on the results of the study, several aspects of internal control implemented by business owners for each MSME have been implemented well, but some are still not good enough. The implementation of internal control at UMKM A has been carried out quite well due to the values of integrity and ethics, which have created a good working bond between employees and owners in managing regulations and policies to achieve common goals. Meanwhile, the implementation of internal control in MSMEs B is still not good because there are still a number of things that have not been implemented properly, such as the authority and division of employee responsibilities, because there is no clear division of tasks and responsibilities and there are no written regulations governing this matter. By implementing policies, training, supervision, and creating a good work environment, owners will be able to detect fraud early on, increase employee compliance, increase openness and transparency, and build trust so as to prevent fraud in MSMEs.Keywords: Business management, internal control, MSMEs, and fraud.